TELEVISI DAN PERGESERAN KONSEP SEKS NORMATIF : PENGARUH TAYANGAN PORNOMEDIA TELEVISI DAN AGAMA TERHADAP SIKAP SEKS MAHASISWA S1 KOTA SURABAYA - Wahyudianata, Megawati (Scriptura, 2007)
Research on television and changes of the normative sex%2C basically wanted to answer two issues namely: (1) Does presentation of television porno-media have effects on sex attitudes of S1 students in Surabaya City? (2) Does religion have effects on alternate variables of television porno-media presentation and sex attitudes midst S1 students of Surabaya City? Whereas objective of the research was to find out effects of television porno-media presentation on sex attitude of S1 students of Surabaya City and analyze effects of religion as an alternate variables on relatedness of television porno-media presentation with sex attitudes midst S1 students of Surabaya city. Based on research results and statistical tests that had been carried out%2C it was found out that television porno-media presentation had effects on sex attitudes of S1 students of Surabaya city. And in view of path test%2C it could be concluded that religion had effects as an alternate variable for a variable of television porno-media presentation and variable of sex attitudes midst S1 students of Surabaya City. Abstract in Bahasa Indonesia : concept of normative sex%2C media effects